Search for leptoquark pairs decaying into nunu+jets in pp collisions at square root[s] = 1.8 TeV. - Abazov,VM; Abbott,B; Abdesselam,A; Abolins,M; Abramov,V; Acharya,BS; Adams,DL; Adams,M; Ahmed,SN; Alexeev,GD; Alton,A; Alves,GA; et al. (Phys Rev Lett, 2002)
We present the results of a search for leptoquark (LQ) pairs in (85.2+/-3.7) pb(-1) of pp collider data collected by the D0 experiment at the Fermilab Tevatron. We observe no evidence for leptoquark production and set a limit on sigma(pp-->LQLQ-->nunu+jets) as a function of the mass of the leptoquark (m(LQ)). Assuming the decay LQ-->nuq, we exclude scalar leptoquarks for m(LQ) < 98 GeV/c(2), and vector leptoquarks for m(LQ) < 200 GeV/c(2) and coupling which produces the minimum cross section, at a 95% confidence level.